Inhaled Corticosteroid and Secondary Glaucoma: A Meta-analysis of 18 Studies - Ishii, Mai (Allergy Asthma Immunol Res, 2021)
PURPOSE: Guidelines and systematic reviews frequently warn of inhaled corticosteroid (ICS)-induced glaucoma. However, most of the published studies deny it. METHODS: We performed a systematic review of randomized, cohort, nested-case control, cross-sectional studies by using Meta-analyses of Observational Studies in Epidemiology statement. Four major databases, PubMed, EMBASE, Cochrane Search Manager, and the Web of Science Core Collection as well as meta-analysis were used. Studies comparing incidence, prevalence and intraocular pressure (IOP) between patients who were treated with and without ICSs were included. A random-model meta-analysis was performed using the inverse variance method. RESULTS: Out of 623 studies screened, 18 with 31,665 subjects were finally included. No significant difference between the 2 groups was observed for crude glaucoma incidence (odds ratio [OR], 0.95; 95% confidence interval [CI], 0.86–1.04; P = 0.26; I (2) = 0%; P for heterogeneity = 0.57) as a primary endpoint, adjusted glaucoma incidence (OR, 0.90; 95% CI, 0.65–1.24; P = 0.64), crude prevalence (OR, 1.82; 95% CI, 0.23–14.19; P = 0.57), adjusted prevalence (OR, 1.22; 95% CI, 0.50–2.96; P = 0.66), IOP change during ICS treatment (mean difference [MD] +0.01 mmHg; 95% CI, −0.19–0.20; P = 0.95), and single measurement IOP (MD +0.37 mmHg; 95% CI, −0.24–0.97; P = 0.23). Time-to-event analysis for glaucoma development as one of the secondary endpoints (adjusted hazard ratio, 0.52; 95% CI, 0.28–0.96) suggested a reverse association between ICS and glaucoma. CONCLUSIONS: The ophthalmological side effects of ICSs, such as glaucoma and intraocular hypertension, should not be exaggerated. TRIAL REGISTRATION: University Hospital Medical Information Network Center Clinical Trial Registry Identifier: UMIN000040351